Design and Implementation of Self-Cleaning Coated Rooftop Photovoltaic System Supporting Energy Conservation in Small-Medium Enterprises - Agung Wahyuono, Ruri; Magenika Julian, Miga (Jurnal Sosial Teknologi, 2024)
The implementation of rooftop solar power system for SMEs is one step to provide an examplified pilot project so that the clean energy transition in the economic sector can also be realized. However, difficult operations and maintenance for rooftop solar power plant require a self-cleaning coating design to passively clean the surface of the solar cell module and hence, the performance of rooftop solar power system is maintained. In this research, the design of a rooftop solar power system utilizes global climate data, i.e., air temperature data and duration of sunlight. Long-term trends in solar radiation levels were analyzed using the Mann-Kendall test and Sen's slope analysis to assess the long-term solar energy potential. The self-cleaning layer utilized a mixture of ZnO/TiO2 (1:1) dispersed in water/ethanol (7:3). The results of implementing the solar energy system for food-based SMEs in Indramayu showed a positive response. Solar energy supply from rooftop solar power system with the application of ZnO/TiO2 self-cleaning coating can save energy usage by up to 30% of the monthly electricity costs charged for MSME operations and domestic needs. The ZnO/TiO2 self-cleaning layer is found to be able to maintain rooftop solar power system performance of up to 85% during 9 months of observation.